Relevansi Nilai-nilai Karakter dalam Film PK Karya Rarjkumar Hirani terhadap Pendidikan Islam - Asrori Asrori (Universitas Sebelas Maret, 2020)
Character is a differentiator between humans and other creatures and is the ultimate goal of education. Learning about character values in the digital era is not only through verbal learning or direct examples from teachers, but can also use film as a media. The purpose of this reasearch is to describe the character values in PK films and their relevance to Islamic education. This research is descriptive qualitative research with content analysis technique. The results of this study are the discovery of some character values such as religious, honest, responsibility, hard work, pluralism, helping others. These values have relevance to the values of I'tiqadiyyah or Ilahiyah and values of Khuluqiyyah or Insaniyah in Islamic education.